Core Loss Calculation in Amorphous High Frequency High-Power Transformers with Different Topologies - Bahmani, Mohammad Amin (My University, 2011)
Using offshore wind farm to generate electrical power was a hot research topic over the last decade. The generated power is to be delivered to the consumers and one of the most effective ways of doing this is via a dc link to the shore that requires introducing a dc-dc convertor to the transmission system. A key element of such a convertor is a high frequency high power transformer (HFHP). The idea of using high frequency transformers in conjunction with wind turbines stems from the fact that the required core cross-section is inversely proportional to the frequency of the applied flux and, hence, a HFHP transformer can be expected to be much lighter in comparison with the same transformer operating at power frequency. Increasing the frequency of the applied voltage and currents thus has a large impact on the transformer. The challenge is that due to eddy currents in the core the flux is also displaced from the core with increasing frequency. This increases the stray flux and losses. Additionally capacitive effects become more important at high frequency. Practical implementation of the idea is challenging because design principles of such power transformers (including magnetic system, HV insulation, cooling, etc.) have not been established yet. Therefore, fundamental research is required to work out criteria for materials selection and to understand behaviour of transformer components in a wide frequency range (up to 10 kHz) and under high electrical stresses. Analytical and empirical equations for core loss calculation have been compared and the equivalent elliptical loop (EEL) method has been selected to be used in finite element Ansoft Maxwell 3D for core loss calculation. The main advantage of this method is considering the effects of minor loops inside the main hysteresis loop due to magnetic flux reversal. Different topologies of the magnetic core have been compared based on core loss computed with the EEL method. These topologies are Hexa core, E core with 3 limbs, E core with 5 limbs, Polyphase Y and single phase C core.
Keywords: Energi; Elektroteknik; Energy; Electrical engineering